Analisa Cash Ratio pada Perusahaan Manufaktur Bidang Makanan dan Minuman yang Terdaftar di Bei Tahun 2019 – 2023 - Hasanudin, Hasanudin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
A manufacturing company is a type of company whose main activity is to purchase raw materials and process them into semi-finished or finished goods that have a selling value. In 2023, there are 12 sectors based on the classification of each company listed on the Indonesia Stock Exchange. This study analyzes the cash ratio in three food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The research method used is descriptive qualitative method with literature study research type. The results showed that the company's cash ratio fluctuated during the period. PT Indofood Sukses Makmur Tbk has the best cash ratio in 2022 at 87%, while PT Mayora Indah Tbk has the best cash ratio in 2020 with a ratio of 109%. PT Garudafood Putra Putri Jaya Tbk has the lowest cash ratio in 2019 of 37% and the highest ratio in 2020 of 65%. The research conclusion shows that the company's ability to meet its short-term obligations varies and the cash ratio can be used as an indicator of the company's liquidity.